2021
DOI: 10.1007/s00415-021-10468-y
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin response in new-onset refractory status epilepticus (NORSE) COVID-19 adult patients

Abstract: Neurological manifestations may be common in COVID-19 patients. They may include several syndromes, such as a suggested autoimmune abnormal response, which may result in encephalitis and new-onset refractory status epilepticus (NORSE). Quickly recognizing such cases and starting the most appropriate therapy is mandatory due to the related rapid worsening and bad outcomes. This case series describes two adult patients admitted to the university hospital and positive to novel coronavirus 2019 (SARS-CoV-2) infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 21 publications
0
27
0
1
Order By: Relevance
“…Of note, the recent COVID-19 pandemic uncovered possible therapeutic approaches for refractory epilepsy. This form of epilepsy developing secondary to COVID-19 is suggested to have an autoimmune etiology and a good response to intravenous immunoglobulin treatment was documented [36]. In terms of serum autoantibodies, we could not identify a statistically significant association between any of the common PM/DM autoantibodies and epilepsy in PM/DM patients.…”
Section: Discussionmentioning
confidence: 65%
“…Of note, the recent COVID-19 pandemic uncovered possible therapeutic approaches for refractory epilepsy. This form of epilepsy developing secondary to COVID-19 is suggested to have an autoimmune etiology and a good response to intravenous immunoglobulin treatment was documented [36]. In terms of serum autoantibodies, we could not identify a statistically significant association between any of the common PM/DM autoantibodies and epilepsy in PM/DM patients.…”
Section: Discussionmentioning
confidence: 65%
“…However, antibody test could be negative in some patients ( Khoo et al, 2020 ). Studies have reported that corticosteroids and intravenous immunoglobulin are considered as first-line therapies for AE treatment ( Manganotti et al, 2021 , Khoo et al, 2020 , Pilotto et al, 2020 , Grimaldi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…5 Two cases responding to intravenous immunoglobulin therapy, and one was associated with anti-NMDA encephalitis. 6,7,8 So far, there is no evidence that COVID-19 infection alone exacerbates seizures in patients with established epilepsy. However, a recent systematic review suggested that patients with pre-existing neurological disorders (including epilepsy) and COVID-19 may develop exacerbation of their neurological problems and also severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%